Lipid profile and carotid artery intima-media thickness in diabetic and non-diabetic ischaemic stroke - Pillai, Preetha R.; Tiwari, Dharmendra; Jatav, O. P.; Rai, Hindeshwari (International Journal of Advances in Medicine, 2017)
Background: Stroke is one of the leading reasons for mortality throughout the world. Measurement of carotid intima media thickness (CIMT) is a reliable marker for the development of atherosclerosis and ischemic stroke (IS). The aim was to study and correlate lipid profile and CIMT in diabetic and non-diabetic IS patients. Methods: An observational study was done including 120 IS patients divided into two groups- diabetes (n=60, diabetic stroke patients) and non-diabetes (n=60, non-diabetic stroke patients) having age >18 years, admitted in Medicine and Neurology wards of G. R. Medical College, Gwalior, Madhya Pradesh, India between August 2015 to August 2016. Detailed history along with investigations such as fasting blood sugar (FBS), post prandial blood sugar (PPBS) and fasting lipid profile including triglycerides (TG), high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL) and total cholesterol (TC) was done. The common and the internal carotid arteries of both sides were evaluated ultrasonographically using a high frequency linear probe. All the data were analysed using IBM SPSS- ver.20 software. Data was expressed as percentage. Analysis was performed using two-way ANOVA and independent sample student t test. Pearson correlation was used to establish the relation between the data. P values <0.05 was considered to be significant. Results: Most common age group among diabetes and non-diabetes IS patients were 51-60 years (26.66%) and 61-70 years (28.33%) respectively with male predominance (75% and 66.67% respectively). Most of the diabetic IS patients had FBS >200 mg/dl (41.66%) and PPBS >250 mg/dl, (50%). Out of 120 IS patients, 55 (45.83%) had CIMT ≤0.8 mm and 65 (54.16%) patients had CIMT >0.8 mm. Lipid parameters including TC (p=0.034), TG (p=0.022), HDL (p=0.039), VLDL (p=0.043) and LDL (p=0.017) were significantly different between groups (p<0.05). Mean CIMT in patients with diabetes and non-diabetes was 1.03±0.255 mm and 0.83±0.54 mm respectively (p=0.006). A significant positive correlation was recorded between CIMT and TC (r=0.36, p=0.006), TG (r=0.48, p=0.0001) and VLDL (r=0.46, p=0.0001) among diabetes stroke patients. Among non-diabetes stroke patients, TC (r=-0.25, p=0.042), TG (r=-0.44, p=0.0003), HDL (r=-0.33, p=0.016) and LDL (r=-0.58, p=<0.001) were negatively correlated and VLDL (r=0.92, p=<0.0001) was positively correlated with CIMT. Conclusions: Lipid parameters including TC, TG, LDL and VLDL were significantly raised in diabetic stroke patients and had a positive correlation with the risk of stroke. CIMT was significantly high in diabetic stroke patients. Correlation of lipid parameters (TC, TG and VLDL) with CIMT in diabetic stroke patients were significantly positively correlated, in non-diabetic ischemic stroke patients’ lipid parameters (TC, TG, HDL and LDL) were negatively correlated.